2021
DOI: 10.1002/srin.202100210
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bentonite and Organic Binders in the Briquetting of Particulate Residues from the Midrex Process for Improving the Thermal Stability and Reducibility of the Briquettes

Abstract: With the aim of achieving sufficient reducibility and thermal stability of briquettes for reuse as feedstock in the Midrex direct reduction process, a defined mixture of residues from the Midrex process is briquetted with an organic binder and bentonite. In the first step, briquetting tests are conducted to investigate the influence of water and binder content on the mechanical properties of the briquettes. Suitable briquettes are then used for reduction tests, where mechanical properties under Midrex‐relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…1) Therefore, in the context of the urgent transformation of global development to zero carbon emission, non-blast furnace ironmaking technologies such as COREX are being vigorously developed. [2][3][4][5] Our previous research has proposed and confirmed that COREX process has a huge advantage in smelting V-Ti bearing burden due to the pure oxygen (without N 2 ) blown into the tuyere. 6) However, COREX also has some problems of insufficient gas flow, excessively high tuyere temperature and high fuel ratio compared with blast furnace, which affects its operation and commercial application.…”
Section: Introductionmentioning
confidence: 75%
“…1) Therefore, in the context of the urgent transformation of global development to zero carbon emission, non-blast furnace ironmaking technologies such as COREX are being vigorously developed. [2][3][4][5] Our previous research has proposed and confirmed that COREX process has a huge advantage in smelting V-Ti bearing burden due to the pure oxygen (without N 2 ) blown into the tuyere. 6) However, COREX also has some problems of insufficient gas flow, excessively high tuyere temperature and high fuel ratio compared with blast furnace, which affects its operation and commercial application.…”
Section: Introductionmentioning
confidence: 75%
“…Peach starch [171] Sodium carboxymethylcellulose [171] Cassava starch [172] Asphalt [173] Pyrolysis oil [174][175][176][177] Molasses [178] Distillers dry grain [178] Crude glycerol [169] Lignosulfonate [169,179] Lignin [168] Lignin powder [167] Pinecones [167] Pyrolytic Lignin [180] Protein, starch, lignin, and molasses [181] Waste cooking oil [182] Deionized water [183] Bentonite [184][185][186][187] Ash [188] Limestone [165] Clay [165] Magnesium oxide [165] Calcium oxide [165] Calcium hydroxide [168] Sodium hydroxide [168] Attapulgite [189] Sodium silicate [165] Magnesium chloride [165] Waste Plastic [190] Kaolin-bentonite-sodium humate [191] Corn straw-sodium hydroxide-MgCl/MgO [191] Coal tar pitch phenolic resins [191] Coal tar pitch and molasses [192] Kang et al [176] reported that when pyrolysis oils are used as a binder, they improve surface morphology and the pellets' physical stability. More precisely, these oils improve pellet drop resistance and compression strength.…”
Section: Organic Binders Inorganic Binders Composite Mixturesmentioning
confidence: 99%
“…This material is used as a binder in the preparation of the pellets. It is considered a suitable inorganic material for the agglomeration of different materials with a similar particle size [19].…”
Section: Bentonitementioning
confidence: 99%